ANALISIS PERBEDAAN KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH PENETAPAN INSENTIF DAN RELAKSASI PAJAK PANDEMI COVID-19 (Studi Empiris pada Perusahaan Multinasional yang Terdaftar di Bursa Efek Indonesia Tahun 2019 dan 2020) - Zuhaf Riany Musdalifah; Endang Kiswara (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the differences in the company’s financial performance before and after the determination of tax incentives and tax relaxations for the Covid-19 pandemic. This study is a replication of the research conducted by Teroui et al (2011) in Tunisia with the equation of variables and indicators of research measurement. There are some differences in the research location, the use of data sources, data analysis methods and also the results of research tests. The population is 212 multinational companies from eleven sectors on the IDX and the sample used in the study is 144 companies with a two- year observation period, 2019 and 2020. The method of this research used is a non-parametric difference test; the Wilcoxon Signed-rank test with the statistical tool SPSS Ver. 23.The results showed the differences in profitability and the implications of corporate tax incentives and relaxation policies variables. While the outputs, debt capacity, capital stock, and employee costs variables did not show any differences in the period before and after the determination of incentives and tax relaxation for the Covid-19 pandemic.